(untitled) (Bangladesh Veterinarian, 2016)
The effect of alcohol and coffee on renal function with pathological changes in kidney was determined in mice. Sixty Albino mice were randomly divided into six equal groups. The mice of group A were maintained as control and remaining five groups were used as treated groups. The mice of control group were supplied with normal mice pellets whereas other groups were supplied with same pellets in addition to 5% coffee (in drinking water), 10% coffee, 10% alcohol, 5% coffee plus 5% alcohol and 10% coffee plus 10% alcohol, for 90 days. The serum creatinine level was significantly (P<0.01) higher in groups supplied with alcohol. There was huge infiltration of reactive cells and mild haemorrhagic spots in kidney of mice that received 10% coffee and 10% alcohol, respectively. It is suggested that long use of high doses of alcohol and coffee impaired kidney function. Bangl. vet. 2015. Vol. 32, No. 2, 42-47